2019
DOI: 10.1038/s41598-019-50775-z
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment and associated morphological changes in pituitary adenylate cyclase activating polypeptide (PACAP)-deficient mice

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is a regulatory and cytoprotective neuropeptide, its deficiency implies accelerated aging in mice. It is present in the auditory system having antiapoptotic effects. Expression of Ca2+-binding proteins and its PAC1 receptor differs in the inner ear of PACAP-deficient (KO) and wild-type (WT) mice. Our aim was to elucidate the functional role of PACAP in the auditory system. Auditory brainstem response (ABR) tests found higher hearing thresholds in KO mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
(83 reference statements)
1
8
0
Order By: Relevance
“…Next, the slices were incubated overnight in 4°C in primary rabbit anti-c-Fos antibody (1:100; SC-52, Santa Cruz, RRID:AB_2106783) in 1% NGS and 0.1% Tween-20 in 0.1 M PBS. This antibody is commonly used in mouse studies (e.g., Howorth et al, 2009;Numa et al, 2019), including in studies of the central auditory system (Fulop et al, 2019). On the next day, the slices were washed 3x5 min with PBS and incubated in secondary antibody (1:500; donkey anti-rabbit Alexa 594) with 1% NGS and 0.1% Tween 20 in PBS for 2 h. Then, the slices were washed in PBS 3x5 min and mounted on a glass slide with a mounting medium (Vectashield H-1200, Vector Laboratories) and the edges were sealed (Cytoseal 60, Richard-Allan Scientific).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Next, the slices were incubated overnight in 4°C in primary rabbit anti-c-Fos antibody (1:100; SC-52, Santa Cruz, RRID:AB_2106783) in 1% NGS and 0.1% Tween-20 in 0.1 M PBS. This antibody is commonly used in mouse studies (e.g., Howorth et al, 2009;Numa et al, 2019), including in studies of the central auditory system (Fulop et al, 2019). On the next day, the slices were washed 3x5 min with PBS and incubated in secondary antibody (1:500; donkey anti-rabbit Alexa 594) with 1% NGS and 0.1% Tween 20 in PBS for 2 h. Then, the slices were washed in PBS 3x5 min and mounted on a glass slide with a mounting medium (Vectashield H-1200, Vector Laboratories) and the edges were sealed (Cytoseal 60, Richard-Allan Scientific).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Recent studies have shown that PACAP KO animals display earlyonset and a more generalized form of systemic amyloid deposition throughout the body in various organs (Reglodi et al 2018b), and PACAP deficiency makes the articular cartilage structure more prone to degenerate (Szegeczki et al 2019;Lauretta et al 2020). PACAP-deficient mice also display accelerated hearing impairment compared to wild-type mice (Fulop et al 2019a). The protective effect of endogenous PACAP has also been described in retinal toxic, ischemic, metabolic, and inflammatory lesions (Kawaguchi et al 2010;Szabadfi et al 2012;Vaczy et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Using noise-exposed mice with PACAP deletion or over-expression of the human PACAP transgene, we identified a protective effect of endogenous PACAP against acute noise-induced hearing loss. Interestingly, a recent study demonstrated that endogenous PACAP is essential in the maintenance of hearing during aging in mice (Fulop et al, 2019 ). Also, previous results from the same lab have already demonstrated an anti-apoptotic effect of PACAP against oxidative stress-induced chicken cochlear cell death in vitro (Racz et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%